PYROLYSIS REACTOR ANALYSIS OF MATERIAL PRODUCTION RESULTS BURN WITH 3KG CAPACITY - M Kitabika Damaputra; Dony Susandi; Asep Rachmat (Universitas Majalengka, 2022)
Garbage is one of the factors that damage the environment, basically garbage increases along with the increase in population and the level of consumption of the processing community Waste is two sides of a coin, waste recapitulation in 2020 in Majalengka Regency is data from the DLH (Environmental Service) Majalengka states that the population is 1,250,180 people produce 14,857 tons/day or 178,285 tons/year waste and transported or processed waste only 34,675 tons/year, this pyrolysis process is a thermochemical decomposition of organic material or inorganic processes that take place without air or oxygen where the raw material will undergo breakdown chemical structure into the gas phase, the plastic pyrolysis process requires several tools, namely a reactor as a combustion without air or oxygen from plastic so that it becomes gas, parameters including temperature which affects the change of plastic into gas, the pressure on the reactor tube caused by the thermal decomposition of plastic into pyrolysis gas, these parameters in the pyrolysis process are mutually tangent because the temperature of the combustion of the reactor will determine the resulting pressure, This is because the hotter the combustion in the reactor, the faster the pyrolysis process occurs, 180 minutes of the oil process produced by PP type plastic is 800 ml while LDPE type plastic is 500 ml, the results on the two plastics are different due to the difference in melting point temperature between types of plastic PP and LDPE, these parameters can be seen in the heat transfer in the pyrolysis reactor of 3.798 x 109 with turbulent flow type